Methodology for the Formation of a Digital Model of the Life Cycle of an Offshore Oil and Gas Platform - Didenko, Nikolay; Skripnuk, Djamilia; Merkulov, Viktor; Kikkas, Kseniia N.; Skripniuk, Konstantin (Resources (Basel), 2023)
This article systematizes scientific views on the problems associated with the conditions and patterns of creating a digital model of a sophisticated engineering and technical complex. The main elements of a digital model of the life cycle of an offshore oil and gas platform are considered. An interdisciplinary approach to the study of the essence of the subject space of the life cycle of an offshore oil and gas platform is substantiated on the basis of modeling the subject space of the life cycle of an offshore oil and gas platform using alternative graphs and information technologies. New concepts have been introduced into scientific circulation that reveal the essence of a digital model of the life cycle of an offshore oil and gas platform: life cycle cost, life cycle duration, and the scientific and technical level of the offshore oil and gas platform. The main provisions of the concept of the virtual life cycle of an offshore oil and gas platform are considered. Based on modeling the subject area of the life cycle of an offshore oil and gas platform by alternative graphs, is shown the relationship between the stages of the life cycle. The technology of model-based design of the virtual life cycle of an offshore oil and gas platform is proposed. The developed model of the life cycle of an offshore oil and gas platform based on the display of the life cycle by alternative graphs makes it possible to choose solutions for each stage based on criteria common to the life cycle of an offshore oil and gas platform. A cyclic procedure for managing a virtual life cycle model of an offshore oil and gas platform has been developed. The digital model of the life cycle of an offshore oil and gas platform is constantly updated following the change in physical prototypes, which increases the accuracy of decisions based on it. The application of the model in practice will significantly reduce the number of full-scale tests of everything related to the manufacture of the real material part of a platform.